Combustion Analysis of the Renewable Fuel HVO and RME with Hydrogen Addition in a Reciprocating Internal Combustion Engine - Stanislaw Szwaja; Saugirdas Pukalskas; Romualdas Juknelevicius; Alfredas Rimkus (Energies, 2025)
In the era of depletion of fossil fuels, there is an intensive search for renewable fuels for the internal combustion engine, which is the most efficient thermal machine in the power range of several kW to several MW. Hence, this article discusses the results of research on the combustion of renewable fuels such as hydrotreated vegetable oil (HVO) and the rapeseed methyl ester (RME) with the addition of hydrogen, injected in its gaseous form into the intake manifold. The thermodynamic analysis presented in the article discusses progress in the combustion process of these fuels depending on the hydrogen content. The parameters for diesel fuel combustion are given as a reference point. Based on the obtained results, one can conclude that adding hydrogen increases the maximum combustion pressure in the cylinder and significantly accelerates the combustion process in the premixed combustion phase, thus reducing the share of the diffusion combustion phase. This significantly affects exhaust toxic emissions. In connection with this, a shortening of the flame kernels development phase was observed, calculated as the time expressed by the crank angle, to release heat of 10%, and a slight extension of the main combustion phase, managed as the period of the heat released from 10 to 90% was observed as well.